Nurses’ Therapeutic Communication and Its Effect on Hospitalized Patients’ Satisfaction - Farah Yasmine Ainun Nisa; Ratna Dwi Wulandari; Tatin Wahyanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Patient satisfaction is one of the hospital indicators used to measure hospital quality. However, the result of patient satisfaction measurement in the inpatients' rooms showed that the level of patient satisfaction was below target. Therefore, it's crucial to carry out a series of therapeutic communication processes as an effort to improve patient satisfaction. This study sought to determine the effect of nurses' therapeutic communication on patient satisfaction in the inpatients' rooms. This was an analytical study with a cross-sectional design conducted from May to June 2022 at Muji Rahayu Hospital, with 70 respondents obtained using systematic random sampling technique. Primary data was gathered from questionnaires that had been distributed to respondents earlier. SPSS was used to analyze data with the Spearman test used. This study revealed that as many as 48,6% of nurses carried out therapeutic communication well. This study also showed that the orientation phase (p=0.000) and work phase (p=0.000) affected patient satisfaction, while the termination phase had no effect (p=0.081). Collectively, there was a significant effect between therapeutic communication on patient satisfaction (p=0.000). Abstrak: Kepuasan pasien merupakan salah satu indikator pengukuran mutu rumah sakit, tetapi hasil dari pengukuran kepuasan pasien di ruang rawat inap RS Muji Rahayu menunjukkan bahwa tingkat kepuasan pasien masih dibawah target. Oleh karena itu perlu dilaksanakan serangkaian proses komunikasi terapeutik sebagai upaya untuk meningkatkan kepuasan pasien. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh dari komunikasi terapeutik perawat terhadap kepuasan pasien di ruang rawat inap RS Muji Rahayu Surabaya. Penelitian ini berjenis analitik dengan rancang bangun cross-sectional yang dilakukan pada bulan Mei–Juni 2022 di RS Muji Rahayu Surabaya dengan jumlah 70 responden dan diambil menggunakan teknik systematic random sampling. Data primer diperoleh dari kuesioner yang disebar ke responden. Analisis data menggunakan SPSS dengan uji Spearman. Hasil dari penelitian ini menunjukkan bahwa sebanyak 48,6% perawat telah melakukan komunikasi terapeutik dengan baik. Penelitian ini juga menunjukkan bahwa fase orientasi (p=0,000) dan fase kerja (p=0,000) berpengaruh terhadap kepuasan pasien, tetapi fase terminasi tidak berpengaruh (p=0,081). Secara bersama-sama, terdapat pengaruh yang signifikan antara komunikasi terapeutik terhadap kepuasan pasien (p=0,000).